The Effectiveness of Talking Stick Method To Improve Students’ Speaking Ability at English Departement of Universitas Muhammadiyah Sorong - Mabel, Hori; Ruslan, Ruslan; Bawawa, Marni; Saputra, Dian (JOLIES : Journal of Linguistic and English Studies, 2024)
This research was conducted to find out the effectiveness of Talking Stick Method to Improve Students’ Speaking Ability at English Department of Sorong Muhammadiyah University. The method of this research was descriptive quantitative. The design of this research was pre experimental used one group pre-test post-test design. This study used purposive sample, the sample consists of 19 students. The findings of this research showed the use of talking stick method improved the students’ speaking ability at English Department of Sorong Muhammadiyah University because there was a significant difference between the results of pretest and posttest, where the mean score of pretest was 1.93 and the mean score of posttest was 2.83. To compare the mean score between pretest and posttest, the researcher used t-test formula and the result of t-test formula was 10.112. By using the degree of significance 1% or 0.01 in the t-table it was obtained 2.861. Thus, alternative hypothesis (H1: 10.112 > 2.861) was accepted because t-test value was higher than t-table value and null hypothesis (Ho: 2.861 < 10.112) was rejected. Therefore, The writer would like to conclude that the use of Talking Stick Method could improve students’ speaking ability at English Department of Sororng Muhammadiyah University